COOPERATIVE TRANSPORT SYSTEMS INCLUDING SOLUTION FOR TRAFFIC ACCIDENTS PREVENT AND OTHER TRANSPORT EXTERNALITIES IN THE REGIONAL TRANSPORT (Perner's Contacts, 2015)
Population mobility on the specific area has quantitative and qualitative site. It is necessary to ensure satisfactory mobility for all people living in a particular area and usually it is also necessary to ensure safety - this topic includes solutions for accidents prevent. For this issue solving it is necessary to evaluate aspects like ownership of a vehicle (automobile, motorcycle, bicycle) and also required qualification to use it (driving license, good physical condition, etc.). Some residents are not able to meet those conditions for objective and subjective reasons. It is necessary to create conditions for the development of public transport, and also create cooperative use of transport systems, including solutions to prevent traffic accidents and other transport externalities.
Keywords: mobility; transport services; regional transportation